Management of interstitial pregnancy in the era of laparoscopy: a meta-analysis of 855 case studies compared with traditional techniques - Greg Marchand; Ahmed Taher Masoud; Anthony Galitsky; Ali Azadi; Kelly Ware; Janelle Vallejo; Sienna Anderson; Alexa King; Stacy Ruther; Giovanna Brazil; Kaitlynne Cieminski; Sophia Hopewell; et al. (Korean Society of Obstetrics and Gynecology, 2021)
Interstitial pregnancy is a rare, life-threatening condition that requires high clinical suspicion for diagnosis. Most cases are discovered after complications have occurred. Many authors have described laparoscopic management. Although previous systematic reviews have compared the attributes and complications associated with interstitial pregnancy, we endeavored to complete the first systematic review and meta-analysis to compare the laparoscopic treatment of interstitial pregnancy with the open approach in the modern age of laparoscopic surgery. We systematically searched PubMed, ClinicalTrials.gov, Scopus, Web of Science, and Cochrane until June 2020 using relevant keywords and screened them for eligibility. We found a statistically significant difference in blood loss between laparoscopic and open surgery (168 mL compared to 1,163 mL). Further, cumulative meta-analysis has revealed that blood loss in laparoscopy has been decreasing over time from 1991 to 2020. Laparoscopic patients took less operative time (63.2 minutes) compared to laparotomy patients (78.2 minutes). Patients in the laparoscopic group spent less time hospitalized (3.7 days) compared to laparotomy patients (5.2 days). Our findings add strength to the position that laparoscopic approaches to interstitial pregnancy can be considered first-line in most situations. The laparoscopic approach was found to have a mean blood loss of 168 mL, and this blood loss seems to decrease over time. Increased gravidity and duration of amenorrhea are positive factors that increase bleeding during the procedure. We are unable to find enough high-quality data to significantly compare successful pregnancy following surgery or risk of mortality in these populations.